2021
DOI: 10.3390/molecules26133849
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone Ameliorates Neuropathic Pain Symptoms via Cannabinoid and PPAR Receptors Using In Vivo and In Silico Models

Abstract: Neuropathic pain is a chronic pain condition persisting past the presence of any noxious stimulus or inflammation. Zerumbone, of the Zingiber zerumbet ginger plant, has exhibited anti-allodynic and antihyperalgesic effects in a neuropathic pain animal model, amongst other pharmacological properties. This study was conducted to further elucidate the mechanisms underlying zerumbone’s antineuropathic actions. Research on therapeutic agents involving cannabinoid (CB) and peroxisome proliferator-activated receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Additionally, in a neuropathic pain model, miR-7a has been observed to be the most greatly decreased miRNA in the dorsal root ganglion, and upregulation of miR-7a resulted in recovery from neuropathic pain [37]. It has been experimentally shown that miR-137-3p regulates CDK6 [38] and KIT [39], while miR-378a-3p regulates specific pain-related genes including casp9 [40][41][42], IGF1R, MAPKAPK2, ODC1 [43], PPARA [44,45], and TP53 [46][47][48][49]. The miRNAs identified in this study are potential therapeutic targets and treatments for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a neuropathic pain model, miR-7a has been observed to be the most greatly decreased miRNA in the dorsal root ganglion, and upregulation of miR-7a resulted in recovery from neuropathic pain [37]. It has been experimentally shown that miR-137-3p regulates CDK6 [38] and KIT [39], while miR-378a-3p regulates specific pain-related genes including casp9 [40][41][42], IGF1R, MAPKAPK2, ODC1 [43], PPARA [44,45], and TP53 [46][47][48][49]. The miRNAs identified in this study are potential therapeutic targets and treatments for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically used daily dosages of 10 mg up to 80 mg/d have proven lipid lowering ability [ 31 ] and reflect doses of ~150–1200 µg/kg (orally administered) with an oral bioavailability of ~20% [ 32 ]. The dosage of PPAR-α antagonist GW6471 (1 mg/kg) was also chosen based on the literature [ 18 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to our best knowledge, no study has examined the successful PPAR-α inhibition by reduced transcription levels of its target proteins so far. As a proven inhibition of PPAR-α enables a clear conclusion regarding the dependency or independency of the observed pravastatin-mediated effects, this should be the subject of further studies [ 18 , 33 , 34 , 35 , 36 ].…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to the compounds mentioned above, other natural phytochemicals showed potential PPARs ligand activity in research studies ( Table 1 ). Terpenoids such as 1,8-cineole [ 7 , 179 ], gingerol [ 7 ], cinnamaldehyde [ 180 ], carvacrol [ 181 ], zerumbone [ 182 ], oridonin [ 183 ], tanshinone IIA [ 184 ], pedunculoside [ 185 ], and lycopene and β -carotene [ 186 ] acted as dual PPARs activators for exhibiting antiatherosclerotic, antiadipogenic, anti-inflammatory, anticancer, hepatoprotective, and antihyperlipidemia effects. Interestingly, betulinic acid (a triterpenoid) had PPAR γ and PPAR α antagonist activity in 3T3-L1 cells to boost glucose uptake and osteogenesis, along with adipogenesis inhibition [ 187 ].…”
Section: Phytochemicals With Ppar Modulation Activitiesmentioning
confidence: 99%